Spaciousness: its Aspects and Impacting Factors - Saleheh Bokharaee, (صفه)
Spaciousness is one of the factors that directly affect users’ satisfaction of a particular space. A key question in this area is that how a space with a given area could be perceived as spacious rather than cramped. This paper presents a literature review on the theory and practical hints on how spaciousness could be enhanced and measured. In particular, it is argued that spaciousness directly correlates with certain physical factors such as area, light, ceiling height, wall proportions, openings, color, etc. A series of examples are given to demonstrate the positive versus negative impacts of these factors on the perceived spaciousness. The paper concludes with enumerating areas for further research.